2012
DOI: 10.1089/dia.2011.0229
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia, but Not Glucose Variability, Relates to Vascular Function in Children with Type 1 Diabetes

Abstract: Hypoglycemia, but not glucose variability, during continuous glucose monitoring relates to impaired vascular endothelial function in children with type 1 diabetes. Hypoglycemia may be an additional risk factor for early cardiovascular disease, but the effect of glucose variability, independent of glycosylated hemoglobin, on vascular function remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 27 publications
2
29
2
Order By: Relevance
“…In agreement with Di Flaviani et al [33], established postprandial hyperglycemia is a detrimental factor in reduced flow-mediated vasodilation and activation of oxidative stress is associated with increased glucose variability in type 2 diabetes. In contrast, Peña et al [34] reported that glucose variability, as measured by CGM, is not associated with vascular function in type 1 diabetes. This highlights possible differences in the role of glucose variability in arteriosclerosis in type 1 and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…In agreement with Di Flaviani et al [33], established postprandial hyperglycemia is a detrimental factor in reduced flow-mediated vasodilation and activation of oxidative stress is associated with increased glucose variability in type 2 diabetes. In contrast, Peña et al [34] reported that glucose variability, as measured by CGM, is not associated with vascular function in type 1 diabetes. This highlights possible differences in the role of glucose variability in arteriosclerosis in type 1 and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…Studies looking at flow mediated vasodilatation and glyceryl trinitrate have elegantly demonstrated impaired vasodilatation in children and adolescents . Associations with both hyperglycemia and hypoglycemia and reduced endothelial function have been made as well as an improvement of endothelial function with folate . However, folate supplementation was only successful when folate was deficient, with no effect of folate on vascular function in folate replete children .…”
Section: Introductionmentioning
confidence: 99%
“…116 Endothelial dysfunction has been demonstrated in numerous studies in adolescents with T1DM. 96,117 Nonultrasound methods for assessing endothelial function, including peripheral arterial tonometry, 118,119 and laser flow Doppler studies 120 have demonstrated similar case-control differences. Poor endothelial function was associated with higher HbA 1c 121 and poor fitness level 122 but was not related to inflammation.…”
mentioning
confidence: 97%